Chitosan Derivatives with Mucoadhesive and Antimicrobial Properties for Simultaneous Nanoencapsulation and Extended Ocular Release Formulations of Dexamethasone and Chloramphenicol Drugs - Aikaterini Karava; Maria Lazaridou; Stavroula Nanaki; Georgia Michailidou; Evi Christodoulou; Margaritis Kostoglou; Hermis Iatrou; Dimitrios N. Bikiaris (MDPI AG, 2020)
The aim of this work was to evaluate the effectiveness of neat chitosan (CS) and its derivatives with 2-acrylamido-2-methyl-1-propanesulfonic acid (AAMPS) and [2-(methacryloyloxy)ethyl]dimethyl-(3-sulfopropyl)ammonium hydroxide (MEDSP) as appropriate nanocarriers for the simultaneous ocular administration of dexamethasone sodium phosphate (DxP) and chloramphenicol (CHL). The derivatives CS-AAMPS and CS-MEDSP have been synthesized by free-radical polymerization and their structure has been proved by Fourier-Transformed Infrared Spectroscopy (FT-IR) spectroscopy. Both derivatives exhibited low cytotoxicity, enhanced mucoadhesive properties and antimicrobial activity against Staphylococcus aureus (S.aureus) and Escherichia coli (E. coli). Encapsulation was performed via ionic crosslinking gelation using sodium tripolyphosphate (TPP) as the crosslinking agent. Dynamic light scattering measurements (DLS) showed that the prepared nanoparticles had bimodal distribution and sizes ranging from 50-200 nm and 300-800 nm. Drugs were encapsulated in their crystalline (CHL) or amorphous (DexSP) form inside nanoparticles and their release rate was dependent on the used polymer. The CHL dissolution rate was substantially enhanced compared to the neat drug and the release time was extended up to 7 days. The release rate of DexSP was much faster than that of CHL and was prolonged up to 3 days. Drug release modeling unveiled that diffusion is the main release mechanism for both drugs. Both prepared derivatives and their drug-loaded nanoparticles could be used for extended and simultaneous ocular release formulations of DexSP and CHL drugs.